2002
DOI: 10.1637/0005-2086(2002)046[0442:iotpoo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Presence of Ornithobacterium rhinotracheale in Chickens in Turkey and Determination of the Seroprevalance of the Infection Using the Enzyme-Linked Immunosorbent Assay

Abstract: In this study, the presence of Ornithobacterium rhinotracheale infection in the avian population in the Marmara and the Western Black Sea region was investigated. Trachea samples were randomly obtained from 96 chickens sent to slaughterhouses. The seroprevalance of the infection was determined in 384 blood sera. Ninety-six of these 384 samples belonged to animals from which trachea samples were obtained. Eleven (11.46%) O. rhinotracheale were isolated in 96 trachea samples taken from 10 different flocks brough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
4
11
0
4
Order By: Relevance
“…These findings are lower than those results of Heeder et al (2001) and Turan and Ak (2002), but is in agreement with the findings of Sakai et al (2000) and Ryll et al (1997). The differences in the results of reports might be due to that most of our samples were not taken from young chickens and in the early stage of infection in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are lower than those results of Heeder et al (2001) and Turan and Ak (2002), but is in agreement with the findings of Sakai et al (2000) and Ryll et al (1997). The differences in the results of reports might be due to that most of our samples were not taken from young chickens and in the early stage of infection in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Sakai et al (2000) found that 13.5%, 13.9% and 12.7% of the tested sera of broilers, broiler breeders and layers, respectively were positive. Another study showed antibodies in 64.4% of the tested sera of broiler and layer flocks (Turan and Ak, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, five of the field strains tested were identified as ORT serotype A and only one strain as serotype B. Scientists reported that serotype A was found to have the highest prevalence especially in chickens in other countries as well as in Turkey (Dudouyt et al, 1995;Van Empel et al, 1997;Turan and Ak, 2002). Erganis et al (2002) reported that of the two strains isolated in Turkey, one was serotype B and the other could not be serotyped.…”
Section: Discussionmentioning
confidence: 52%
“…Turkyilmaz (2001) suggested that three isolates were ORT serotype I. Turan and Ak (2002) showed that 90.9% were determined to be serotype A and one strain could not be serotyped. Our results are in agreement with the results reported in other countries and Turkey (Dudouyt et al, 1995;Van Empel et al, 1997;Erganis et al 2002;Turan and Ak, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotics of choice are tetracycline, chlortetracycline and amoxiciline. High seroprevalences of O. rhinotracheale infection have been recorded in some countries in Europe and Asia, especially in Germany 26% (Hafez and Sting 1996), in Turkey 62.5% (Turan and Ak 2002) and in Iran 44.2% (Allymehr 2006), mostly in broiler flocks.…”
mentioning
confidence: 99%